Analisa Tegangan pada Desain Empat Mata Potong untuk Mesin Pencacah Plastik Menggunakan Metode Elemen Hingga - Hendra Hendra; Syahril Al Qirom; Sidik Susilo; Kurnia Nugraha; Hernadewita Hernadewita; Frengki Hardian (Politeknik Negeri Padang, 2023)
Excessive use of plastic materials eventually causes problems related to the accumulation of plastic waste. One way to deal with plastic waste is to crush it into smaller pieces using a plastic chopper machine. The purpose of this research is to redesign the cutting blade of the crushing machine by varying the thickness of the cutting blade, the number of cutting blades of the crushing machine, and varying the cutting tooth material to get maximum stress and displacement [1-3]. From previous research it was shown that stress and deformation occurred at the number of 2 and three cutting chisel blades [1-2] and the tilt position of 4 cutting chisel blades [3]. In this research uses simulation the finite element method by a solid work design application. The thicknesses variations are 5 mm, 7 mm, and 10 mm and the number of cutting blades amounting four. The number of cutting blades used is four because of the simple design and able to carry out more cutting processes. The materials used are AISI 1045, HSS 18%, and JIS SKD 11. From the results is the recommended material thickness is 10 mm because it is able to accept less stress than 5 mm and 7 mm. The results in terms of the mechanical strength of the simulation state that all are safe to use. If it is based on mechanical strength, the recommended material is AISI 1045 coMPared to 18% HSS STEEL and JIS SKD 11. However, from economic factors, 18% HSS is a recommendation to be chosen as a cutting tooth material.